Explaining Growth and Inequality in Factor Income: The Philippines Case - Hyun H. Son (Asian Development Bank (ADB), 2008)
This paper analyzes the relationship between growth and inequality of factor income in the Philippines, focusing on the role played by the labor market. It proposes a decomposition methodology that explores linkages between growth in income and labor market performance in terms of labor force participation, employment, working hours, and productivity. This paper introduces a methodology that provides a direct linkage between growth, inequality, and labor market characteristics. It provides empirical analysis using both the Family Income and Expenditure Survey and Labor Force Survey, covering the period 1997–2003.
hdl:11540/1776
Keywords: 330; Wirtschaftswachstum; Einkommensverteilung; Arbeitsmarkt; Dekompositionsverfahren; Philippinen